Species Visitation at Quail Feeders and Guzzlers in Southern New Mexico - Dale Rollins; Ben D. Taylor; Troy D. Sparks; Tom E. Wadell; George Richards (National Quail Symposium Proceedings, 2017)
Providing supplemental feed and water are sometimes used to manage scaled quail (Callipepla squamata) in the Chihuahuan Desert even though their biological and economical efficacies are questionable. Seasonal visitation rates of scaled quail and various nontarget species are important parameters affecting the efficacy of feeding and watering practices. However, empirical data on visitation by scaled quail at feeders and guzzlers are lacking. We used video surveillance to assess species visitation at free-choice quail feeders and guzzlers in south-central New Mexico during 2002. Scaled quail accounted for 19.4 and 21.5% of visitations at feeders and guzzlers, respectively. Mourning doves (Zenaida macroura), nongame birds, and desert cottontails (Sylvilagus audubonni) were the primary nontarget consumers at this site. Relative to similar studies of feeder visitation by northern bobwhite (Colinus virginianus) in west Texas, quail feeders tended to be more efficacious (i.e., a greater proportion of the feeder visitations were by quail) in this study. While the biological impacts of feeders and guzzlers remain poorly documented, their use by scaled quail suggests they are important foci within the birds’ home ranges. Video surveillance technology permits managers to make data-based decisions on the biological and economic worth of such management efforts. We also describe novel uses for video surveillance relative to facilitating reconnaissance of radiotagged quail whose radios had malfunctioned. Future research should assess the potential for using video surveillance at guzzlers to estimate chick survival in scaled quail.
Keywords: Callipepla squamata; Chihuahuan desert; guzzlers; scaled quail; supplemental feeding; surveillance camera; water developments